Part III: Digestibility of eight hybrid sorghum grains and three hybrid corns - R.L. McCollough; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1972)
Apparent coefficient of digestion (COD) was determined for eight hybrid sorghum grains and three hybrid corns named in Part I.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Digestibility; Hybrid sorghum; Hybrid corn